Analysing the macroeconomic drivers of stock market development in the Philippines - Sin-Yu Ho; N. M. Odhiambo (Cogent Economics & Finance, 2018)
This paper analyses the macroeconomic drivers of stock market development in the Philippines during the period 2001Q4-2016Q4. In particular, the paper examines the impact of banking sector development, inflation rate, exchange rate, economic growth, trade openness and stock market liquidity on the development of the Philippine stock market. Theoretical and empirical literature reveals diverse views on the relationship between each determinant and stock market development. In addition, the Philippine stock market has experienced remarkable growth in recent decades. However, there is no similar study on this country in the literature. The paper, therefore, enriches the literature by investigating the macroeconomic drivers of stock market development in the Philippines using the ARDL bounds testing procedure. The results show that trade openness has had a negative impact on Philippine stock market development in the long run, whereas banking sector development and the exchange rate have had positive impacts on the development of the Philippine stock market in the short run. These findings are robust to alternative specifications of the model.
Keywords: C22; E44; G23; 330; macroeconomic drivers; stock market development; the Philippines; ARDL bounds testing